2001
DOI: 10.1097/00005537-200108000-00025
|View full text |Cite
|
Sign up to set email alerts
|

Expression of p16, nm23‐H1, E‐cadherin, and CD44 Gene Products and Their Significance in Nasopharyngeal Carcinoma

Abstract: Detecting the expressions of those gene products may provide clinically valuable information for therapeutic strategy and for predicting the prognosis of patients with NPC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 38 publications
3
22
1
Order By: Relevance
“…We found over-expression of cyclin D1 in 26% and the lack of expression of p16 in 96% of recurrent NPC specimens. While the level of over-expression of cyclin D1 (26%) in recurrent NPC specimens was similar to the levels of over-expression (30% [7] to 66% [9]) found in primary untreated NPC, the lack of expression of p16 in recurrent NPC specimens (96%) was significantly higher than those typically reported for primary untreated NPC (40% to 70%) [9][10][11][12].…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…We found over-expression of cyclin D1 in 26% and the lack of expression of p16 in 96% of recurrent NPC specimens. While the level of over-expression of cyclin D1 (26%) in recurrent NPC specimens was similar to the levels of over-expression (30% [7] to 66% [9]) found in primary untreated NPC, the lack of expression of p16 in recurrent NPC specimens (96%) was significantly higher than those typically reported for primary untreated NPC (40% to 70%) [9][10][11][12].…”
Section: Discussionsupporting
confidence: 64%
“…Over-expression of cyclin D1 and/or loss of p16 has been reported in several studies on NPC. These studies found an increased level of cyclin D1 expression in 30% [7] to 66% [9] and the lack of expression of p16 in 40% to 70% of previously untreated NPC specimens [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…EBV microRNA-associated degradation also involves p53 downstream effectors TP53INP1 and MASPIN, suggesting that p53-dependent tumor suppression may be inhibited despite accumulation of wild-type p53 in NPC. 29 EBV microRNAs may also influence metastasis by targeting cell adhesion genes such as E-cadherin, 52 a frequently down-regulated gene in metastatic NPC. 53 Although we were unable to derive both RNA and protein from our NPC cases because of small biopsy samples, previous studies demonstrated only modestly inhibited protein production, rarely finding >4-fold reduction in protein levels.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, these etiological factors may induce aberrant expression of cell adhesion molecules (CAMs) in NPC, since CAMs govern the social behaviors of cells and altered expression of CAMs affects the motility and invasiveness of many tumor cells in vitro and metastasis in vivo (Cavallaro et al, 2004). For examples, up-regulation of ICAM (Yu et al, 2004) and down-regulation of E-cadherin (Huang et al, 2001;Li et al, 2004) and connexin 43 (Yi et al, 2006) correlates with the progression of NPC; however, the expression of CD44 does not (Huang et al, 2001). …”
mentioning
confidence: 99%